2010
DOI: 10.1074/mcp.m110.001586
|View full text |Cite
|
Sign up to set email alerts
|

SH2 Domains Recognize Contextual Peptide Sequence Information to Determine Selectivity

Abstract: Selective ligand recognition by modular protein interaction domains is a primary determinant of specificity in signaling pathways. Src homology 2 (SH2) domains fulfill this capacity immediately downstream of tyrosine kinases, acting to recruit their host polypeptides to ligand proteins harboring phosphorylated tyrosine residues. The degree to which SH2 domains are selective and the mechanisms underlying selectivity are fundamental to understanding phosphotyrosine signaling networks. An examination of interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
137
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 61 publications
4
137
0
Order By: Relevance
“…Specifically, we tested whether a PROTAC can selectively distinguish between an activated versus a quiescent receptor tyrosine kinase-signaling pathway. Because phosphorylated tyrosine residues can serve as ligands for the binding of phosphotyrosine-binding (PTB) and Src homology 2 (SH2) domain-containing proteins (8), a cellpermeable PROTAC molecule that incorporates a specific tyrosine kinase substrate sequence may do the same (9). Thus, phosphorylation of such a PROTAC by a receptor tyrosine kinase (RTK) could generate a binding site for a downstream PTB or SH2 domain-containing protein and its subsequent recruitment to the ubiquitin/proteasome degradation pathway for destruction, thereby disrupting tyrosine kinase signaling ( Fig.…”
mentioning
confidence: 99%
“…Specifically, we tested whether a PROTAC can selectively distinguish between an activated versus a quiescent receptor tyrosine kinase-signaling pathway. Because phosphorylated tyrosine residues can serve as ligands for the binding of phosphotyrosine-binding (PTB) and Src homology 2 (SH2) domain-containing proteins (8), a cellpermeable PROTAC molecule that incorporates a specific tyrosine kinase substrate sequence may do the same (9). Thus, phosphorylation of such a PROTAC by a receptor tyrosine kinase (RTK) could generate a binding site for a downstream PTB or SH2 domain-containing protein and its subsequent recruitment to the ubiquitin/proteasome degradation pathway for destruction, thereby disrupting tyrosine kinase signaling ( Fig.…”
mentioning
confidence: 99%
“…Yaffe et al [22], in studying the phosphopeptide-binding protein 14-3-3, found that substrates adhered to one of two mutually exclusive sequence modes. Liu et al [23] have demonstrated that SH2 domains, which recognize and bind to phosphotyrosine-containing peptides, will vary in their specificity at some with a phosphotyrosine along with a leucine or a proline in the þ3 position. Proline at the þ2 position, however, is allowed only when the identity of the þ3 position is leucine and not proline.…”
Section: Discussionmentioning
confidence: 99%
“…The first assumption is that amino acids that contribute positively to an interaction are more important than amino acids that contribute negatively to binding. A recent study by Liu et al suggested that amino acids that block SH2 domain interaction may be as important in contributing to SH2 domain selectivity as amino acids that contribute to binding [18]. A second assumption is that the context of amino acids is not important in defining interaction specificity.…”
Section: Editorialmentioning
confidence: 99%